Development of a horseradish peroxidase-nanobody fusion protein for visual detection of ochratoxin A by dot immunoassay. Issue 56 (11th September 2020) - Chen, Qi; Wang, Yuanyuan; Mao, Fujing; Su, Benchao; Bao, Kunlu; Zhang, Zeling; Xie, Guifang; Liu, Xing
Abstract : The horseradish peroxidase-nanobody fusion protein was developed as a promising immunological diagnostic reagent for toxic low-molecular-weight compounds in food. Abstract : Ochratoxin A (OTA) is a common cereal mycotoxin that seriously threatens food safety and public health. Herein a horseradish peroxidase-nanobody fusion protein (HRP-Nb) retaining antibody and enzyme activity was obtained after inclusion body denaturation and renaturation and enzyme reconstitution, which served both as the primary antibody and reporter enzyme and was applied to develop a membrane-based dot immunoassay (HN-DIA) for OTA visual detection. Based on the optimal experimental conditions, the HN-DIA could be finished in 10 min with a cut-off limit of 50 μg kg −1 in rice and oat samples by eye. The HN-DIA showed high selectivity for OTA and had good accuracy and reproducibility in the recovery experiments. Spiked sample analysis results of the HN-DIA and high performance liquid chromatography (HPLC) correlated well with each other. Therefore, the proposed HN-DIA has the potential for rapid screening of OTA and other small molecule pollutants in food and the environment by naked eye.